Determination of the fuels dielectric properties, their mixtures and soil. Their impact on use of energy resources in the determination of environmental contamination (2019)
The study of the dielectric properties of materials is one of the main tools currently used for their characterization, both structurally and from the point of view of molecular interactions. In our University it has been used in the study of fuels and their mixtures: gasoline-alcohol and fossil biodiesel-Diesel, since it allows determining the mechanisms of molecular interaction present in the mixtures, both of polar and non-polar substances, which determines the optimal concentrations of the components in the mixture, in terms of their stability, free energy, entropy, enthalpy of evaporation, as well as the energy of cohesion and dielectric relaxation mechanisms. These properties of fuels are what determine, in the first instance, the combustion efficiency. On the other hand, the same technique applied to soils makes it possible to determine the humidity and, more importantly, the contamination of the soils by fuels and lubricants. Then, with the same experimental setup, the structural and dynamic properties of fuels, their mixtures and lubricants can be determined, which are closely related to the efficient use of these, as well as the contamination of soils by these same chemical agents. The results of the dielectric characterization and its relationship with the molecular interaction energies of the alcohol-gasoline mixtures, biodiesel-fossil Diesel and the determination of the influence of humidity and fuel contamination on the dielectric properties of the floors.